Impact of cryoprotective agents on human gut microbes and in vitro stabilized artificial gut microbiota communities - Giulia Alessandri; Sonia Mirjam Rizzo; Leonardo Mancabelli; Federico Fontana; Giulia Longhi; Francesca Turroni; Douwe vanSinderen; Marco Ventura (Microbial Biotechnology, 2024)
Abstract The availability of microbial biobanks for the storage of individual gut microbiota members or their derived and artificially assembled consortia has become fundamental for in vitro investigation of the molecular mechanisms behind microbe–microbe and/or microbe–host interactions. However, to preserve bacterial viability, adequate storage and processing technologies are required. In this study, the effects on cell viability of seven different combinations of cryoprotective agents were evaluated by flow cytometry for 53 bacterial species representing key members of the human gut microbiota after one and 3 months of cryopreservation at −80°C. The obtained results highlighted that no universal cryoprotectant was identified capable of guaranteeing effective recovery of intact cells after cryopreservation for all tested bacteria. However, the presence of inulin or skimmed milk provided high levels of viability protection during cryoexposure. These results were further corroborated by cryopreserving 10 artificial gut microbiota produced through in vitro continuous fermentation system technology. Indeed, in this case, the inclusion of inulin or skimmed milk resulted in a high recovery of viable cells, while also allowing consistent and reliable preservation of the artificial gut microbiota biodiversity. Overall, these results suggest that, although the efficacy of various cryoprotective agents is species‐specific, some cryoprotectants based on glycerol and the addition of inulin or skimmed milk are preferable to retain viability and biodiversity for both single bacterial species and artificial gut microbiota.